Building AI Literacy for Sustainable Teacher Education - Olivia Rütti-Joy; Georg Winder; Horst Biedermann (Forum Neue Medien in der Lehre Austria, 2023)
This article highlights the significance of AI Literacy for promoting sustainable teacher education in an AI-driven world. Given the rapid progress of AI, a crucial aspect of organisational development for teacher education institutions involves fostering AI Literacy among teaching staff, and enabling them to use and teach AI ethically and responsibly. We underscore the necessity for teacher education institutions to create opportunities for developing AI Literacy as a fundamental goal for sustainable development. Further, we explore recommendations for sustainable organisational and professional development as well as future research directions.